Une appréciation critique du traitement des dépenses de consommation dans le modèle CANDIDE 1.1 - Carré, Ronald (L'Actualité économique, 1976)
AbstractThis paper begins by discussing what ought to be the approach to the problem of forecasting in the medium term. The author emphasizes the advantages of a very detailed breakdown of sectors. He then considers certain econometric problems which arise when forecasting consumption in the medium term. He contrasts the formulation of the consumer sector in CANDIDE with that of two other types of model and compares the results of each.The author proposes an alternative way of treating consumption in CANDIDE which would take into account different categories of households. Finally, he discusses how to resolve problems of organization of the data, of modelling, and of estimation which may arise when using such an approach.